A Double Blind Randomized Clinical Trial of Remote Ischemic Conditioning in Live Donor Renal Transplantation. Issue 31 (August 2015) - Nicholson, Michael L.; Pattenden, Clare J.; Barlow, Adam D.; Hunter, James P.; Lee, Gwyn; Hosgood, Sarah A.; Giuseppe, Lucarelli.
<x xml:space="preserve">Abstract</x> Abstract Ischemic conditioning involves the delivery of short cycles of reversible ischemic injury in order to induce protection against subsequent more prolonged ischemia. This randomized controlled trial was designed to determine the safety and efficacy of remote ischemic conditioning (RC) in live donor kidney transplantation. This prospective randomized clinical trial, 80 patients undergoing live donor kidney transplantation were randomly assigned in a 1:1 ratio to either RC or to a control group. RC consisted of cycles of lower limb ischemia induced by an arterial tourniquet cuff placed around the patient's thigh. In the RC treatment group, the cuff was inflated to 200 mm Hg or systolic pressure +25 mm Hg for 4 cycles of 5 min ischemia followed by 5 min reperfusion. In the control group, the blood pressure cuff was inflated to 25 mm Hg. Patients and medical staff were blinded to treatment allocation. The primary end-point was renal function measured by estimated glomerular filtration rate (eGFR) at 1 and 3 months posttransplant. Donor and recipient demographics were similar in both groups (P < 0.05). There were no significant differences in eGFR at 1 month (control 52 ± 14 vs RC 54 ± 17 mL/min; P = 0.686) or 3 months (control 50 ± 14 vs RC 49 ± 18 mL/min; P = 0.678) between the control and RC treatment groups. The RC technique did not cause any serious adverse effects. RC, using the protocol described here, did not improve renal function after live donor kidney transplantation.